A Proposed Method for Accurate 3D Analysis of Cochlear Implant Migration Using Fusion of Cone Beam CT - Dees, Guido; van Hoof, Marc; Stokroos, Robert (Frontiers in Surgery, 2016)
Introduction The goal of this investigation was to compare fusion of sequential cone beam CT volumes to the gold standard (fiducial registration) in order to be able to analyze clinical CI migration with high accuracy in three dimensions. Materials and Methods Paired time-lapsed cone beam CT volumes were performed on five human cadaver temporal bones and one human subject. These volumes were fused using 3D Slicer 4 and BRAINSFit software. Using a gold standard fiducial technique, the accuracy, robustness and performance time of the fusion process were assessed. Results This proposed fusion protocol achieves a sub voxel mean Euclidean distance of 0.05 millimeter in human cadaver temporal bones and 0.16 millimeter when applied to the described in vivo human synthetic data set in over 95% of all fusions. Performance times are less than two minutes. Conclusion Here a new and validated method based on existing techniques is described which could be used to accurately quantify migration of cochlear implant electrodes.